Role of EBNA-3 Family Proteins in EBV Associated B-cell Lymphomagenesis - Bhattacharjee, Shaoni; Ghosh Roy, Shatadru; Bose, Priyanka; Saha, Abhik (Frontiers in Microbiology, 2016)
Epstein-Barr virus (EBV) is highly ubiquitous in human population and establishes a lifelong asymptomatic infection within the infected host unless the immune system is compromised. Following initial infection in the oropharyngeal epithelial cells, EBV primarily infects naive B-lymphocytes and develops a number of B-cell lymphomas particularly in immune-deficient individuals. In vitro, EBV can also infect and subsequently transform quiescent B-lymphocytes into continuously proliferating lymphoblastoid cell lines (LCLs) resembling EBV-induced lymphoproliferative disorders in which a subset of latent transcripts are detected. Genetic studies revealed that EBNA-3 family comprising of three adjacent genes in the viral genome – EBNA-3A and -3C, but not -3B, are critical for B-cell transformation. Nevertheless, all three proteins appear to significantly contribute to maintain the overall proliferation and viability of transformed cells, suggesting a critical role in lymphoma development. Apart from functioning as important viral transcriptional regulators, EBNA-3 proteins associate with many cellular proteins in different signalling networks, providing a suitable platform for lifelong survival of the virus and concurrent lymphoma development in the infected host. The chapter describes the function of each these EBV nuclear antigen 3 proteins employed by the virus as a means to understand viral pathogenesis of several EBV-associated B-cell malignancies.